2008
DOI: 10.3171/jns.2008.109.12.1165
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial molecular changes in a rodent model of arteriovenous malformation

Abstract: The AVF model has a "nidus" with endothelial molecular changes similar to those observed in human AVMs, supporting its use as a model for studying the effects of radiosurgery on AVMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…However, this does not mean a 15-Gy dose of radiation is enough for vascular obliteration in AVMs. Clinical work has demonstrated that a margin dose of [16][17][18][19][20][21][22][23][24][25] Gy is necessary to achieve a satisfactory occlusion rate. 10,44 More work with smaller titrations of radiation doses and larger animal numbers per group is required to find the optimal radiation dose for vascular targeting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not mean a 15-Gy dose of radiation is enough for vascular obliteration in AVMs. Clinical work has demonstrated that a margin dose of [16][17][18][19][20][21][22][23][24][25] Gy is necessary to achieve a satisfactory occlusion rate. 10,44 More work with smaller titrations of radiation doses and larger animal numbers per group is required to find the optimal radiation dose for vascular targeting.…”
Section: Discussionmentioning
confidence: 99%
“…25,33,38 A highly discriminating target, which dominantly expresses on AVM endothelium, is required for the success of this technique. We have investigated the molecular characteristics of the endothelial surface of AVM vessels 20,39,40 and, although differences were found in comparison with normal blood vessels, no target with adequate discriminating power has been found to date. However, radiation-induced molecular changes on the endothelial surface may be a promising source of targets for vascular targeting.…”
mentioning
confidence: 99%
“…It is possible that sufficient endothelial changes are caused by the shear stress from the high blood flow in these vessels 23 to enable the LPS/sTF treatment to induce thrombosis. Among rats in this group, thrombosis durability appeared less robust; rates of vessel occlusion at the later time points were lower.…”
Section: 15mentioning
confidence: 99%
“…23,31,33,49,55,56 The AVM model creation has been described in detail. 23,47,54,60 Briefly, rats were anesthetized, and an anterior cervical approach was used to expose the left common carotid artery and external jugular vein. Blood flow through the common carotid artery was measured by using a 1-mm Doppler ultrasonic probe (Transonic Systems Inc.).…”
mentioning
confidence: 99%
“…We have developed an animal model that shares hemodynamic, structural, and molecular characteristics with human AVMs. 6,20 These characteristics make this model suitable for studying the early molecular responses of the AVM endothelial phenotype to radiation. However, before studying the molecular responses, one must understand the morphological, hemodynamic, and histological changes that occur after radiation treatment.…”
mentioning
confidence: 99%